The Family as a Source of Social Capital in Three Balkans Countries: Key Indicators - Goran Miladinov (Studies in Social Science & Humanities, 2022)
The paper faces the family social capital concept. This is a concept on which demography starts to reflect only recently. In this paper, after revising existing theoretical approaches and literature, an operationalization of the concept of family social capital is proposed. Using aggregate panel data for three Balkans countries this research demonstrates the importance of family as a source of social capital. The results from the two underlying components of our PCA are associated to the underlying theoretical constructs of family social capital. In that way, these components appear to reflect two different aspects: component 1 via CBR and POP14 variables reflects strong demographic ties and the family and the component 2 which through GGFCE reflects the direct help for families and children by the State. Macedonia is the country which has the most positive correlation with the CBR and POP14. In contrast, Greece is typically least associated with these two variables under consideration.